2021
DOI: 10.2147/jir.s299083
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to High-Fat Style Diet Induced Renal and Liver Structural Changes, Lipid Accumulation and Inflammation in Intact and Ovariectomized Female Rats

Abstract: Purpose We hypothesized that low estrogen levels aggravate obesity-related complications. Diet-induced obesity can cause distinct pathologies, including impaired glucose tolerance, inflammation, and organ injury that leads to fatty liver and chronic kidney diseases. To test this hypothesis, ovariectomized (OVX) rats were fed a high-fat style diet (HFSD), and we examined structural changes and inflammatory response in the kidney and liver. Methods Sprague-Dawley female r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Reportedly, a study proves that HFD intake increases the obese gene product known as leptin, total body fat, and calorie intake ( 23 ). This, in turn, manifests in the changes in histological and morphological changes of organs, liver, and renal markers ( 24 ). Thus, HFD is considered to be one of the most studied methods to induce obesity ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, a study proves that HFD intake increases the obese gene product known as leptin, total body fat, and calorie intake ( 23 ). This, in turn, manifests in the changes in histological and morphological changes of organs, liver, and renal markers ( 24 ). Thus, HFD is considered to be one of the most studied methods to induce obesity ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that ovariectomy increases susceptibility to the severity of chronic arthritis and local inflammation because of the resulting lack of estrogen, and also that estradiol-replacement therapy can induce a protective anti-inflammatory effect and improves innate immune responses in ovariectomized arthritic mice ( 54 ). In additional, the structural changes and inflammatory response in the kidney and liver have been shown to be significantly increased by a high-fat diet and exacerbated by ovariectomized conditions ( 55 ). Estrogen is thought to play an important regulatory role in the innate and adaptive immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…The double immunofluorescence was performed according to the method as previously described. 33,34 The deparaffinised, rehydrated and antigen retrieved sections were blocked with 2.5% normal horse serum provided in the kit (Vector Laboratories, Burlingame, CA, USA) for 30 min at room temperature. The slides were incubated with first primary antibodies like caspase-3 (NB100-56708; Novus Biologicals, Littleton, CO, USA) at ratio of 1:1000 for 2 h at room temperature, then the slides were washed with PBS for three times.…”
Section: Methodsmentioning
confidence: 99%